2004
DOI: 10.1097/01.phm.0000130033.91894.5a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treadmill Walking Speed on Lateral Gastrocnemius Muscle Firing

Abstract: Many patients with upper motor neuron lesions (e.g., stroke and traumatic brain injury) walk at speeds much slower than those commonly described in the literature for normal gait. At the slow walking speed of 0.5 m/sec, we have measured noticeable changes in the electromyographic timing profile of the gastrocnemius muscle. Given the importance of appropriate plantar flexor firing patterns to maximize walking efficiency, understanding the speed-related changes in gastrocnemius firing patterns may be essential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Interestingly, our finding of the prolonged firing duration of MG poststroke as compared to baseline value (Fig. 4a) was in line with a simulation model study from Clancy and coworkers who set 0.5 m/s as a typical speed for persons after stroke (Clancy et al, 2004). They found that the profile of the main peak of MG was broadened, with a delayed onset and completion, at the lower speed.…”
Section: Symmetery Indexsupporting
confidence: 93%
“…Interestingly, our finding of the prolonged firing duration of MG poststroke as compared to baseline value (Fig. 4a) was in line with a simulation model study from Clancy and coworkers who set 0.5 m/s as a typical speed for persons after stroke (Clancy et al, 2004). They found that the profile of the main peak of MG was broadened, with a delayed onset and completion, at the lower speed.…”
Section: Symmetery Indexsupporting
confidence: 93%
“…However, computerized algorithms can fail to accurately detect burst onset in experimental data, indicating that some of these techniques may not be sensitive enough to improved SNR. In several studies, EMG burst properties were analyzed with visual inspection instead of a computerized algorithm (Clancy et al 2004; Latash et al 1995; Tedroff et al 2008; Vasseljen et al 2006), suggesting that algorithm validation using artificially generated EMG signals may not be sufficient to test robustness and accuracy of onset detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These data are consistent with the idea that muscle activation increases with increasing moments and that a greater muscle mass is activated more effectively at all contraction speeds. Gait data also supports this contention [56,57]. High moments and muscle mass require greater activation compared with the activation needed during isokinetic contractions of increasing speed.…”
Section: Discussionmentioning
confidence: 63%